Implementasi Model Pembelajaran Make a Match pada Siswa Kelas XI-B1 SMAN 9 Surabaya untuk Meningkatkan Hasil Belajar Teks Cerpen - Reza Dwi Nurlitasari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This study uses the Make a Match learning methodology in class XI-B1 SMAN 9 Surabaya to increase student learning outcomes on short story text content. 36 students participated in two cycles of the study. Following the implementation of the Make a Match learning paradigm, the results demonstrated a significant increase in student participation and learning outcomes. Despite some students still falling short of the KKM, the number of students in cycle 1 who received good and very good categories grew. Every student outperformed the KKM in cycle 2, with 41.7% placing them in the outstanding group and 58.3% in the good category. This approach worked well to increase overall student participation and learning results.